School Starting Age, Maternal Age at Birth, and Child Outcomes - Peter Fredriksson; Kristiina Huttunen; Björn Öckert (Institute of Labor Economics (IZA), 2021)
This paper analyses the effects of maternal school starting age and maternal age-at-birth on children's short and long-term outcomes using Finnish register data. We exploit a school-starting-age rule for identification. Mothers who are born after the school entry cut-off give birth at higher age, but total fertility and earnings are unaffected. Being born after the cut-off reduces gestation and, hence, child birth weight. The effects on birth weight and gestation are rather small, however, suggesting that the long-run impacts are limited. Accordingly, we find no impacts on longer-term child outcomes, such as educational attainment and adolescent crime rates. Overall, we interpret this evidence as saying that there are no favorable effects of maternal age at birth on child outcomes.
Keywords: J13; I21; 330; school starting age; fertility; maternal age; birth outcomes; education; crime